Outcomes of intravenous thrombolytic and adjuvant surgery in acute limb ischemia: Review of 23 patients - Demir, Deniz; Kahraman, Nail (Journal of Surgery and Medicine, 2019)
Aim: Today, combined thrombolytic and surgical adjuvant embolectomy is known to have positive results in acute limb ischemia (ALI) treatment. In thrombolytic therapy, the intra-arterial method is generally used. In our study, we performed an intravenous thrombolytic and / or adjuvant surgical embolectomy in patients with failed bypass or diffuse aorta vascular disease who were unable to perform catheter directed thrombolytic therapy (CDT) due to technical difficulties. We evaluated the mortality and morbidity results of the patients. Methods: Retrospective cohort study was planned. This study consists of patients treated for ALI between January 2014 and September 2018. First, the intravenous thrombolytic treatment was performed. The patients who failed this treatment were additionally treated with surgical embolectomy. The patients were in Rutherford Class IIa and IIb. Results: A total of 23 ALI patients were included in the study. Thrombolytic treatment was performed on all of the patients. Twelve (52%) patients who failed thrombolytic treatment were also treated with surgical adjuvant embolectomy. In the first month, two patients (8.7%) required major amputation. In follow-up period of one year, a total three patients (13%) required major amputation and one patient (4.3%) had intracranial hemorrhage. Conclusions: ALI, despite all the developments in its treatment, is still a life threatening disease. This study suggests that our rate of amputation, hemorrhage and extremity rescue are similar or a little lower than the large series of intra-arterial thrombolytic treatments in the literature. Today, the thrombolytic treatment methods have one thing in common which is the use of intra-arterial route. Yet we reckon that as in our study; the patients who cannot be treated with intra-arterial catheterization the intravenous thrombolytic therapy and/or surgical adjuvant embolectomy can be helpful in rescuing those patient’s life and extremity.